Legitimate wrongs and Marketing Communication Strategies of Universities in Nigeria - Ade-Johnson, Christiana Shade (NIU Journal of Humanities, 2020)
Studies have established the fact that marketing communication strategies have the opportunities and power to favourably reinforce or change the beliefs, attitudes, and intentions of target markets relative to the organisations whether or not such organisations have direct contact with the customer. However, in the process of differentiating and creating competitive edge over   competitors, Nigerian Universities are said to be prone to corrupt practices. Therefore, the paper examines the legitimate wrongs committed in the application of marketing communication strategies by Nigerian Universities. Document analysis, observation, interview and questionnaires were used to gather data for the study. It was discovered that the universityâ€™s claim of people as marketing communication strategy is effective. It was also found out that although the lecturers in some of the departments were professional, efficient and responsible, they were not up to the requirement and questionable ways were developed to meet NUC standard.Therefore, NUC is urged to stand up for what it is constituted to carry out as a watchdog in order to prevent the educational system and sector from intractably going down the drain like other Key Words: Corruption, Marketing Communication, Strategy, Programme, People, Physical Facilities